Sediment characteristics of Tanjung Lumpur mangrove forest, Pahang - Saad, Shahbudin; Mohd Yusuf, Nurulnadia; Yunus, Kamaruzzaman; Mohamad Shazili, Noor Azhar (2009)
Sediment characteristics were calculated for Tanjung Lumpur mangrove forest, Kuantan, Pahang. Surface sediment sample was collected from two hundreds and twenty-one points in order to determine the precision of data gathered. The sampling was done in July 2008. Results show that average of eman size (phi) for the study area was 5.88 Ø. The sorting value was quite close to mean size, 3.02 Ø. Meanwhile, the average of skewness was 0.02 Ø and kurtosis was 0.03 Ø.